Pharmacotherapeutic follow-up of patients with type 2 diabetes: Application of the Dáder method in primary health care (Research, Society and Development, 2025)
Introduction: Type 2 diabetes mellitus (T2DM) is a prevalent chronic disease in primary healthcare (PHC) and is often associated with poor treatment adherence and unsatisfactory clinical outcomes. Objective: To assess the impact of a structured pharmacotherapeutic follow-up based on the Dáder method on the clinical indicators of patients with T2DM in Family Health Strategy (FHS) units. Methods: This was a prospective, longitudinal, and quantitative study involving 21 patients diagnosed with T2DM, assisted by a resident pharmacist in two FHS units in southern Mato Grosso, Brazil. The interventions followed the five stages of the Dáder method. Drug-related problems (DRPs), negative outcomes associated with medication (NOMs), capillary blood glucose, fasting blood glucose, and glycated hemoglobin were evaluated. Results: Most DRPs were related to nonadherence (50.87%). Among the NOMs, 80% were due to lack of effectiveness. A non-significant reduction in fasting blood glucose was observed (median, 164–147 mg/dL; p=0.167), along with a significant reduction in glycated hemoglobin (median from 7.8% to 7.5%, p=0.02). A total of 81 interventions were performed, mainly focusing on treatment adherence (35.8%). Conclusion: Pharmacotherapeutic follow-up, even with a small sample size, demonstrated the potential to improve glycemic control and reduce DRPs. These findings reinforce the relevance of pharmacists’ role in PHC and in promoting health in patients with chronic diseases.